The impact of population aging on Russia’s demographic structure - Zhou, Yujia (Global Sustainability Research, 2025)
The population structure of Russia has had different characteristics in a historical period from the Soviet Union era to the Russian Federation era. One of the characteristics is that the ageing population is out of proportion; the other is a remarkable internal migration between different areas of Russia. Therefore, it is necessary that the population structure of Russia needs to be researched carefully as a case study.